Atrazine: cytotoxicity, oxidative stress, apoptosis, testicular effects and chemopreventive Interventions - Abarikwu, Sunny O.; Ezim, Ogechukwu E.; Ikeji, Cynthia N.; Farombi, Ebenezer O. (Frontiers in Toxicology, 2023)
Atrazine (ATZ) is an environmental pollutant that interferes with several aspects of mammalian cellular processes including germ cell development, immunological, reproductive and neurological functions. At the level of human exposure, ATZ reduces sperm count and contribute to infertility in men. ATZ also induces morphological changes similar to apoptosis and initiates mitochondria-dependent cell death in several experimental models.When in vitro experimental models are exposed to ATZ, they are faced with increased levels of reactive oxygen species (ROS), cytotoxicity and decreased growth rate at dosages that may vary with cell types. This results in differing cytotoxic responses that are influenced by the nature of target cells, assay types and concentrations of ATZ. However, oxidative stress could play salient role in the observed cellular and genetic toxicity and apoptosis-like effects which could be abrogated by antioxidant vitamins and flavonoids, including vitamin E, quercetin, kolaviron, myricetin and bioactive extractives with antioxidant effects. This review focuses on the differential responses of cell types to ATZ toxicity, testicular effects of ATZ in both in vitro and in vivo models and chemopreventive strategies, so as to highlight the current state of the art on the toxicological outcomes of ATZ exposure in several experimental model systems.